Spine Surgery - Meyer, Bernhard; Rauschmann, Michael (Springer, 2019)
We are very excited to introduce this new book on spinal surgery, which follows the curriculum of the EUROSPINE basic and advanced diploma courses. The approach we take is a purely case-based one, in which each case illustrates the concepts surrounding the treatment of a given pathology, including the uncertainties and problems in decision-making. The readers will notice that in many instances a lack of evidence for a given treatment exists. So decisions taken are usually not a clearcut matter of black or white, but merely different shades of gray. Probably in a lot of cases, there is often more than one option to treat the patient. The authors were asked to convey this message to the reader, giving him a guidance as what would be accepted within the mainstream. In addition, the reader is provided with the most updated literature and evidence on the topic. Most of the authors are teachers in the courses of EUROSPINE or other national societies with often vast clinical experience and have given their own perspective and reasoning. We believe that the readers will profit very much from this variety and bandwidth of knowledge provided for them in the individual chapters. We have given the authors extensive liberty as to what they consider the best solution for their case. It is thus a representative picture of what is considered standard of care for spine pathologies in Europe. We hope that this book will be an ideal complement for trainees to the courses they take.
A Case-Based Approach